Work fatigue in urban bus drivers - Teresa Makowiec-Dąbrowska; Jadwiga Siedlecka; Elżbieta Gadzicka; Agata Szyjkowska; Marta Dania; Piotr Viebig; Marcin Kosobudzki; Alicja Bortkiewicz (Nofer Institute of Occupational Medicine, 2015)
Background: Bus drivers are a special group of professional drivers who are at a very high risk of fatigue. The aim of the study was to examine whether the driver's subjective assessment of fatigue allows for the determination of its level and identification of its causes. Material and Methods: The study group comprised 45 randomly selected bus drivers (mean age - 43.7±7.9 years, period of employment as drivers - 14.7±8.6 years). Examinations were performed in all subjects four times - before and after work on the "easy" route (outside the city center, small traffic intensity) and before and after work on the "difficult" route (city center, heavy traffic). The fatigue test questionnaire, based on the list of symptoms of fatigue prepared by the Japan Research Committee of Fatigue, was used in the study. Results: The rating of fatigue after the work was significantly higher than that before the work. The profile of fatigue after work was not influenced by the type of route, but the assessment of most symptoms of fatigue reached a higher level after the "difficult" routes and the differences were statistically significant for 7 symptoms. Only the ratings of leg fatigue, feeling of heaviness, and the necessity to squint eyes and gaze with effort reached the higher levels after driving the "easy" routes. It has been found that the level of fatigue was significantly correlated with the job characteristics (driving time, the length of the route, number of stops, etc.) and with the abundance of food ingested and type of beverage (coffee vs. others) drunk prior to driving. Conclusions: The questionnaire used in our study to assess the subjective feeling of fatigue has proved to be a sensitive and useful tool for indicating the level and causes of fatigue. The relationship between the symptoms of fatigue and the characteristics of job and lifestyle shows that actions must be taken by both the employers and employees to prevent fatigue in bus drivers. Med Pr 2015;66(5):661-677